Secondary Intrusion Formation of Multiphase Plumes - Dayang Wang; E. Eric Adams (Frontiers in Marine Science, 2021)
This work presents a new laboratory study for understanding secondary intrusions in multiphase plumes in quiescent, stratified environments. The study is driven by field observations of secondary intrusions during the Deepwater Horizon (DWH) oil spill. The smaller trap heights observed at DWH for secondary versus primary intrusions could have resulted, in part, from decreasing plume buoyancy (due to gas dissolution) and increasing ambient stratification with elevation above the source. We seek additional mechanisms responsible for the observed smaller secondary trap heights through controlled laboratory experiments where buoyancy and ambient stratification are nominally constant throughout. A novel approach is adopted in the experiments to increase the visibility of secondary intrusions, which are traditionally difficult to visualize, thus investigate. The study reveals that a wider plume source width can also cause the secondary intrusions to trap earlier, providing another plausible explanation for the shallower secondary intrusions observed in the field data.